Enhancing Parent-Implemented Functional Communication Training by Assessing Indices of Happiness. Issue 2 (3rd April 2023) - Thomas, Benjamin R.; Bauer, Melanie; Macek, Lauren V.; O'Connor, Julia T.
Abstract: Indicators of well-being can be important measures for improving the treatment of challenging behavior and family quality of life. We examined methods for assessing activities associated with indices of happiness (IOH) in a 5-year-old girl with Down syndrome, to mitigate challenging behavior during parent-implemented functional communication training (FCT). During the initial phase treatment (FCT + extinction), challenging behavior persisted, and parents expressed an emerging sense of hopelessness. Treatment modifications informed by the assessments resulted in a > 90% decrease in challenging behavior, promoted reinforcer schedule thinning, improved cooperation with daily routines, and also increased the child's IOH and parent satisfaction.